FDI in Colombia. Policy and economic effects (2009)
During the past few decades, the competition for foreign direct investments (FDI) has increased around the world. FDI can contribute to economic development not only by being a source of foreign capital, but also by providing employment opportunities, increasing competition, and most importantly transferring skills and knowledge i.e. spillover effects. However, these positive effects are not automatic for host countries and depend largely on the policies in place. Taking a closer look at Colombia, this paper examines polices used to attract FDI and some of the effects FDI has had on the Colombian economy. It is found that FDI has contributed positively to Colombia's economic development but that more needs to be done in order for Colombia to effectively compete for FDI and benefit to a larger extent from it.